A global synthesis of seasonal temperature–size responses in copepods. Issue 8 (4th May 2016) - Horne, Curtis R.; Hirst, Andrew G.; Atkinson, David; Neves, Aitana; Kiørboe, Thomas
Abstract: Aim: Body size is a master trait with significant ecological importance. Seasonal changes in body size within diverse ectothermic species can result from different environmental conditions experienced during ontogeny in subsequent generations. Whilst intraspecific changes in adult size have been well studied under controlled experimental conditions and across geographical ranges, comprehensive analyses of temporal changes are lacking, and there remains considerable unexplained variation in body size responses within aquatic taxa. Using planktonic copepods as an exemplar taxon, we quantify variation in adult body mass within seasonally varying marine and freshwater environments. We describe how size variation relates to temperature, food concentration (chlorophyll‐ a ) and life‐history characteristics, including feeding strategy. Location: Global. Methods: Using a meta‐analytic approach we extract quantitative data from published literature on seasonal size responses of copepods. We analyse competing models to determine the best predictors of these responses, and compare the relative importance of temperature and chlorophyll‐ a concentration in explaining variation in body size. Results: We quantify 140 seasonal size responses from 33 different global locations, representing 48 planktonic copepod species from four taxonomic orders. We find that temperature ( r 2  = 0.50), rather than food ( r 2  = 0.22), is the dominant explanatory variable of changes in adult body size across seasons. A striking outcome is that calanoid copepods, which utilize feeding currents to capture prey, exhibit a four‐fold greater reduction in adult body mass per  °C (−3.66%) compared with cyclopoid copepods (−0.91%), which are ambush feeders. By contrast, species body size or reproductive strategy did not explain variation in the seasonal temperature–size response. Main conclusions: Our findings lead us to suggest that feeding strategies may play a significant role in dictating the magnitude of seasonal temperature–size responses in copepods, with potential implications for other ectotherms with diverse feeding methods. Seasonal temperature–size responses were typically much more variable than responses in laboratory studies that provided excess food, suggesting that field conditions modify the temperature–size response.